Risk factors for carpal tunnel syndrome in patients attending the primary care center of a tertiary hospital in Riyadh, Saudi Arabia: A case-control study - Yaser A Alendijani; Bahaa A Abaalkhail; Abdullah S Binsaeedu; Asim A Alandijani (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Carpal tunnel syndrome (CTS), the most common entrapment neuropathy in the upper extremity, is known to be a multi-factorial disease that raises medical and nonmedical risk factors. The aim of the current study was to determine the risk factors of CTS in patients attending the primary care center at a tertiary hospital. MATERIALS AND METHODS: A case-control study was conducted by reviewing all medical records of patients above the age of 18 years old diagnosed with CTS from 2015 to 2021. The selected cases were evaluated by physical examination and confirmed by a nerve conduction study. Cases and controls were matched by age, gender, and nationality, with a case-to-control ratio of 1:2. Odds ratios were calculated for association between carpel tunnel syndrome and various factors and Chi-sqauare test determined statistical significance. Multiple logistic regression was performed to adjust for confounding. RESULTS: The study recruited 144 cases with a mean age of 53.38 ± 12.20 years and 288 controls with a mean age of 53.80 ± 12.27 years. The majority of subjects were female (84.7%) and of Saudi nationality (68.3%). There was a significant difference in body mass index, employment status, number of years of employment, occupation, mean systolic blood pressure, mean low-density lipoprotein cholesterol level, and mean blood urea level between cases and controls (P < 0.05). Laboratory tests that were found to be significantly associated with CTS in univariate analysis were thyroid-stimulating hormone (crude odds ratio [COR] = 0.828) and urea level (COR = 0.802). In fully adjusted analyses, obesity (adjusted odds ratio [AOR] =3.080), chronic kidney disease (AOR = 3.629), and the use of corticosteroid (AOR = 0.470) were also significantly associated with CTS. CONCLUSION: Similar to the findings of other studies, this study identified several potential risk factors for CTS. More large-scale longitudinal studies are required to establish a precise causal association.